THE UNDERSTANDING OF SANCTIFICATION IN THE WRITINGS OF ELLEN G WHITE - Reymand Hutabarat (Fakultas Filsafat Universitas Advent Indonesia, 2016)
The purpose of this research is to determine Ellen White’s concept of sanctificationor spiritual holiness. Ellen White’s definition of sanctification is biblical, gradual,maturing process and a goal for Christian living. She agrees on the point that twoelements of justification are distinctive even though they are inseparable, and thatjustification is the starting point for spirituality. She points out that sanctificationexperience is as importance to say as for that final judgment because withoutholiness no one can see God. She considers Christian life as pilgrimage and holinessor sanctification as fitness for heaven. She recognizes that sanctification is not justan emotional thing but it must be manifested inwardly and outwardly in a genuineChristian life. She emphasizes the importance of genuine faith that manifests bygood works. She recognizes the Holy Spirit as the agent of sanctification, salvationas restoring man in the image of his Marker, perfection as growing in love rather thatfaultless or sinless, and holy living as Christian purpose of existence